2022
DOI: 10.3390/polysaccharides3010010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Stabilization behind Cardamom Pickering Emulsion Using Nanocellulose

Abstract: Cardamom essential oil (EO) is a rare oil of high scientific and economic interest due to its biofunctionality. This work aims to stabilize the EO by Pickering emulsions with nanocellulose, in the form of nanocrystals (CNC) or nanofibers (CNF), and to investigate the stability and chemical and physical interactions involved in the process. The emulsions were characterized by droplet size, morphology, stability, surface charges, Fourier transform infrared spectroscopy, FT-Raman, nuclear magnetic resonance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Another study that includes Pickering emulsions with nanocellulose in the form of nanocrystals (CNC) or nanofibers (CNF) showed zeta potential values of −45.6 ± 3.6 and −49.9 ± 3.9 mV, respectively, and were considered highly electrostatically stable samples [ 21 ]. The CNF emulsions presented significantly higher values than the CNC emulsions (−18.3 ± 1.4 and −11.1 ± 0.9, respectively), characterised as low-dispersion emulsion at the beginning of agglomeration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study that includes Pickering emulsions with nanocellulose in the form of nanocrystals (CNC) or nanofibers (CNF) showed zeta potential values of −45.6 ± 3.6 and −49.9 ± 3.9 mV, respectively, and were considered highly electrostatically stable samples [ 21 ]. The CNF emulsions presented significantly higher values than the CNC emulsions (−18.3 ± 1.4 and −11.1 ± 0.9, respectively), characterised as low-dispersion emulsion at the beginning of agglomeration.…”
Section: Discussionmentioning
confidence: 99%
“…The CNF emulsions presented significantly higher values than the CNC emulsions (−18.3 ± 1.4 and −11.1 ± 0.9, respectively), characterised as low-dispersion emulsion at the beginning of agglomeration. The study explains the difference based on the chemical composition of the essential oils: the ester as a terminal group and a benzene ring may be responsible for the increase in the negative charges [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardamom (Elettaria cardamomum; CA) is a perennial, aromatic, herbaceous plant belonging to the Zingiberaceae family, whose use is culinary, domestic, and medicinal. It is a species native to southwest Asia (India, Sri Lanka, Malaysia, and Indonesia), Tanzania, and Guatemala, which has been used since ancient times due to its wide variety of antimicrobial, antifungal, antioxidant, analgesic, anti-inflammatory, and anticancer properties associated with the presence of components such as phenols, tannins, terpenoids, flavonoids, and sterols, among others [7][8][9]. Further, in dentistry, it has been reported that CA possesses antibad breath, anticaries, antiseptic, and antimicrobial properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, biopolymer-based delivery systems (e.g., nano-composites, microcapsules, emulsions, hydrogels, films, or membranes, among others) have been widely used for the incorporation of bioactive compounds [6,9,20,[25][26][27][28]. Additionally, membranes or biodegradable films have been designed as controlled-release systems (e.g., would dressing) for various applications in the medical area [6,20,27,29,30].…”
Section: Introductionmentioning
confidence: 99%